2020
DOI: 10.1159/000504039
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Evaluation of Linezolid and Doripenem Clearance with Different Hemofilters

Abstract: Introduction: Renal replacement therapy (RRT) is widely used in the treatment of septic acute kidney injury. However, little is known about how the adsorption properties of hemofilters used in RRT affect antibiotic concentration. Because a cytokine-adsorption membrane is frequently used in RRT, it is important to determine the antibiotic adsorption capacity of this membrane. Objective: The present study aimed to investigate the antibiotic adsorption capacity of different hemofilter membranes by in vitro experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…The mechanism of cytokine adsorption by PMMA seems to involve hydrophobic binding, but this is not fully understood. Additionally, we confirmed that the adsorption capacity of cytokine-adsorbing hemofilters is sufficient for small amounts of substances, such as cytokines, but has no effect on antimicrobial agents, which are millions of times higher than the blood concentration of cytokines, because they exceed the saturation amount [114].…”
Section: Figuresupporting
confidence: 63%
“…The mechanism of cytokine adsorption by PMMA seems to involve hydrophobic binding, but this is not fully understood. Additionally, we confirmed that the adsorption capacity of cytokine-adsorbing hemofilters is sufficient for small amounts of substances, such as cytokines, but has no effect on antimicrobial agents, which are millions of times higher than the blood concentration of cytokines, because they exceed the saturation amount [114].…”
Section: Figuresupporting
confidence: 63%
“…Thus, it was presumed that it was removed in the filtrate beyond the adsorption limit [17]. This phenomenon may be supported by the fact that PMMA membranes show almost no adsorption properties for antibacterial agents [18]. Additionally, the principle of ion adsorption may not work on neutrally charged myoglobin (isoelectric point = 6.9) in the negatively charged AN69ST membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Doripenem is eliminated by the kidney. Doripenem was not absorbed onto AN69ST, polymethylmethacrylate, and polysulfone membranes (Hiraiwa et al, 2020). CVVHD could accelerate the elimination of doripenem (Tanoue et al, 2011).…”
Section: Doripenemmentioning
confidence: 94%